Chronic venous insufficiency, cardiovascular disease, and mortality: a population study. (13th August 2021) - Prochaska, Jürgen H; Arnold, Natalie; Falcke, Andrea; Kopp, Sabrina; Schulz, Andreas; Buch, Gregor; Moll, Sophie; Panova-Noeva, Marina; Jünger, Claus; Eggebrecht, Lisa; Pfeiffer, Norbert; Beutel, Manfred; et al.
Abstract: Aims : Evidence regarding the health burden of chronic venous insufficiency (CVI), its clinical determinants, and impact on outcome is scarce. Methods and results : Systematic phenotyping of CVI according to established CEAP (Clinical-Etiologic-Anatomic-Pathophysiologic) classification was performed in 12 423 participants (age range: 40–80 years) of the Gutenberg Health Study from April 2012 to April 2017. Prevalence was calculated age- and sex-specifically. Multivariable Poisson regression models were calculated to evaluate the relation of CVI with cardiovascular comorbidities. Survival analyses were carried out to assess the CVI-associated risk of death. Replication of findings was done in an independent cohort study (MyoVasc, NCT04064450). The prevalence of telangiectasia/reticular, varicose veins, and CVI was 36.5% [95% confidence interval (CI), 35.6–37.4%], 13.3% [12.6–13.9%], and 40.8% [39.9–41.7%], respectively. Age, female sex, arterial hypertension, obesity, smoking, and clinically overt cardiovascular disease were identified as clinical determinants of CVI. Higher CEAP classes were associated with a higher predicted 10-year risk for incident cardiovascular disease in individuals free of cardiovascular disease ( n = 9923). During a mean follow-up of 6.4 ± 1.6 years, CVI was a strong predictor of all-cause death independent of the concomitant clinical profile and medication [hazard ratio (HR) 1.46 (95% CI 1.19–1.79), P = 0. 0003]. The association of CVI with an increased risk of all-cause death was externally validated in the MyoVasc cohort [HR 1.51 (95% CI 1.11–2.05), P = 0.009]. Conclusion : Chronic venous insufficiency is highly prevalent in the population and is associated with the presence of cardiovascular risk factors and disease. Individuals with CVI experience an elevated risk of death, which is independent of age and sex, and present cardiovascular risk factors and comorbidities. Graphical Abstract: